A VIEW OF THE HISTORY OF UZBEK FOLK PAINTING ART - M.N.Ikromova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The basis of the Uzbek folk applied art is decoration. Ancient historical monuments are beautiful examples of medieval eastern architectural art, which, thanks to its grandeur and uniqueness of patterns, went to the whole world with its elegance. The article talks about the emergence and development trends of Uzbek folk art.